2013
DOI: 10.7567/jjap.52.10mc12
|View full text |Cite
|
Sign up to set email alerts
|

Study of A-Site Disorder Dependent Structural, Magnetic, and Magnetocaloric Properties in La0.7-xSmxCa0.3MnO3 Manganites

Abstract: We report studies on the magnetocaloric effect of samarium doped lanthanum manganites with different Sm-concentrations. Polycrystalline La0.7-x Sm x Ca0.30MnO3 (0≤x≤0.3) samples were prepared using the conventional solid-state reaction method with phase purity and structure confirmed using X-ray diffraction. Temperature dependent magnetization measurements and Arrott analysis reveal first order ferromagnetic transition in parent sample and second order f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…It has been reported that La 0.7−x Sm x Ca 0.3 MnO 3 with x ≥ 0.05 show second order FM -PM transition. 13 It is reported that single crystal of La 0.7 Sr 0.3 MnO 3 (LSMO) shows second-order phase transition from FM-PM with critical exponents β = 0.37 ± 0.045, γ = 1.22 ± 0.03 and δ = 4.25 ± 0.0, which are close to values predicted for conventional Heisenberg ferromagnet. 49 Whereas, La 1−x Ca x MnO 3 manganite undergoes first-order FM-PM transition in the composition range 0.3 ≤ x ≤ 0.4.…”
supporting
confidence: 62%
See 3 more Smart Citations
“…It has been reported that La 0.7−x Sm x Ca 0.3 MnO 3 with x ≥ 0.05 show second order FM -PM transition. 13 It is reported that single crystal of La 0.7 Sr 0.3 MnO 3 (LSMO) shows second-order phase transition from FM-PM with critical exponents β = 0.37 ± 0.045, γ = 1.22 ± 0.03 and δ = 4.25 ± 0.0, which are close to values predicted for conventional Heisenberg ferromagnet. 49 Whereas, La 1−x Ca x MnO 3 manganite undergoes first-order FM-PM transition in the composition range 0.3 ≤ x ≤ 0.4.…”
supporting
confidence: 62%
“…The decrease in the unit-cell volume for these samples compared to La 0.67 Ca 0. 33 13,15,18 From the refinement the estimated atomic positions for the samples are listed in Table I. Microstructure of the samples Fig.…”
Section: A Structure and Morphology Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A prominent feature of these materials is colossal magnetoresistance (CMR) effect, which has been extensively studied in the last few decades [8][9][10][11][12]. Apart from the CMR effect, these compounds have also been found to exhibit the magnetocaloric effect (MCE) under a moderate applied magnetic field [13,[13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%